2018
DOI: 10.1371/journal.pone.0209624
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-reperfusion injury in a rat microvascular skin free flap model: A histological, genetic, and blood flow study

Abstract: Ischemia reperfusion injury is associated with tissue damage and inflammation, and is one of the main factors causing flap failure in reconstructive microsurgery. Although ischemia-reperfusion (I/R) injury is a well-studied aspect of flap survival, its biological mechanisms remain to be elucidated. To better understand the biological processes of ischemia reperfusion injury, and to develop further therapeutic strategies, the main objective of this study was to identify the gene expression pattern and histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…The blocks were subsequently sectioned at 5 µm on the longitudinal plane and stained with hematoxylin and eosin (H&E) and Masson's Trichrome (MT). The main histologic outcome was scored for inflammatory cell infiltration, collagen deposition, edema, hemorrhage, thrombosis, and hair follicle destruction as follows: (0) absent, (1) mild, (2) moderate, (3) severe (Ballestin et al, 2018). At least five microscopic areas were examined to score each specimen, and the total damage scores were calculated as the sum of the scores given for each criterion (Iseri et al, 2008).…”
Section: Histological Stainingmentioning
confidence: 99%
“…The blocks were subsequently sectioned at 5 µm on the longitudinal plane and stained with hematoxylin and eosin (H&E) and Masson's Trichrome (MT). The main histologic outcome was scored for inflammatory cell infiltration, collagen deposition, edema, hemorrhage, thrombosis, and hair follicle destruction as follows: (0) absent, (1) mild, (2) moderate, (3) severe (Ballestin et al, 2018). At least five microscopic areas were examined to score each specimen, and the total damage scores were calculated as the sum of the scores given for each criterion (Iseri et al, 2008).…”
Section: Histological Stainingmentioning
confidence: 99%
“…The selected time for primary ischemia was 8 hours, based on previous studies and our own research experience with this animal model. 2,11,[14][15][16] Macroscopically, our study results showed a significant decrease in flap survival in the I/R control group compared with the control group (p < 0.05). These results conflicted with the histological findings as higher levels of edema formation (p < 0.05), neutrophil infiltration (p < 0.05), and structural damage were observed in the I/R group than in the control group.…”
Section: Discussionmentioning
confidence: 52%
“…As previously reported, skin avulsion leads to damage to soft tissues and blood vessels, which may be associated with different biological processes including ischemia and hypoxia (Ballestin et al, 2018). Therefore, apoptosis pathways mediated by caspase-3 are induced and may exert an immediate influence on the viability of the avulsed skin (Liu et al, 2015).…”
Section: Resultsmentioning
confidence: 78%